2005
DOI: 10.1111/j.1467-842x.2005.tb00770.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial to evaluate the efficacy of a nurse‐provided intervention for hospitalised smokers

Abstract: Objective: Does the provision of a nurse‐based intervention lead to smoking cessation in hospital patients? Methods: At tertiary teaching hospital in Newcastle, Australia, 4,779 eligible (aged 18–80, admitted for at least 24 hours, and able to provide informed consent) and consenting (73.4%) in‐patients were recruited into a larger cross‐sectional survey. 1,422 (29.7%) smokers (in the last 12 months) were randomly assigned to control (n=711) or intervention group (n=711). The brief nurse‐delivered interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 8 publications
1
31
0
Order By: Relevance
“…In most of the research, the basis for sample size was not specified a priori, nor was a retrospective power analysis conducted. Two recent studies 31,39 used power analyses to determine sample size. Most trials did not report "refusal to participate" rates.…”
Section: Methodologic Quality Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In most of the research, the basis for sample size was not specified a priori, nor was a retrospective power analysis conducted. Two recent studies 31,39 used power analyses to determine sample size. Most trials did not report "refusal to participate" rates.…”
Section: Methodologic Quality Of Included Studiesmentioning
confidence: 99%
“…[21][22][23]43 The most recent trials reported some form of biochemical verification of self-reports. 26,28,31,32,33,39 All of the trials used convenience rather than randomly selected samples. Only one of the studies 50 did not let participants know initially that they were going to be part of a smoking-cessation study.…”
Section: Methodologic Quality Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations